1994
DOI: 10.1046/j.1537-2995.1994.34794330012.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of new brochures on blood donor recruitment and retention

Abstract: The brochures may have encouraged previous donors to return, but their use did not significantly increase the recruitment of new donors or the return of temporarily deferred donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Hayes and colleagues 5 compared “foot in the door” versus “door in the face” approaches and found that a small request (e.g., adding the subject’s name to a list of potential donors) followed by a request to donate 1 unit of blood produced significantly more donations than standard practice, whereas a large request (e.g., joining a long‐term donor program with bimonthly donation over 3 years) followed by a request to donate a single unit of blood actually performed worse than standard practice 5 . Two studies used randomized methods to study the effectiveness of brochures and found that brochures alone were relatively ineffective compared with appeals to donors altruism 7,14 . Our finding that a message appealing to empathy or altruism was an effective recruitment approach is consistent with previous literature, although we cannot say that our self‐esteem message was ineffective, just less effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayes and colleagues 5 compared “foot in the door” versus “door in the face” approaches and found that a small request (e.g., adding the subject’s name to a list of potential donors) followed by a request to donate 1 unit of blood produced significantly more donations than standard practice, whereas a large request (e.g., joining a long‐term donor program with bimonthly donation over 3 years) followed by a request to donate a single unit of blood actually performed worse than standard practice 5 . Two studies used randomized methods to study the effectiveness of brochures and found that brochures alone were relatively ineffective compared with appeals to donors altruism 7,14 . Our finding that a message appealing to empathy or altruism was an effective recruitment approach is consistent with previous literature, although we cannot say that our self‐esteem message was ineffective, just less effective.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention group joined the marrow registry at more than two times the rate of the control group receiving no intervention. In 1994 Gimble and coworkers 7 performed a randomized assignment of pairs of similar donor workplaces to the distribution 2 weeks before scheduled blood drives of an informational brochure developed according to Consumer Information Processing Theory. The brochure had no effect on recruitment or return behavior of donors at these workplaces, but analysis of covariates revealed a negative association between the number of blood units collected and blood drives held during vacations or during busy times at the workplace and with making announcements over the workplace loudspeaker before the drive.…”
mentioning
confidence: 99%
“…Educational materials, often in the form of brochures, are used by virtually all blood collection agencies to provide donors with information about the donation process and how to schedule a donation appointment. This material is typically developed independently by each agency, and, with few exceptions, 1 there has been little or no effort to empirically validate and publish the effects that such materials have on current and prospective donors. To address this limitation, we recently published a report on a blood donation brochure 2 that addresses common donor concerns about fear, pain, and potential vasovagal reactions and then suggests empirically validated strategies to cope with these potential barriers to donation 3‐11 .…”
mentioning
confidence: 99%
“…These results are in accordance with other studies, which have demonstrated that educational materials have not always been effective in changing blood donors' attitudes. Some negative findings have already been described by other authors at blood donor settings 21,22 . For instance, pamphlets were not effective in improving the safety and donor eligibility.…”
Section: Discussionmentioning
confidence: 87%